The Structures of the Gauge Bosons after the Symmetry Breaking and the Experimental Data on the Elementary Particles - Mamedov, Fizuli (London Journal of Physics, 2025)
The properties of the gauge bosons built out of the two component spinors are outstandingly well in line with the experimental data on Cabibbo-Kobayashi-Maskawa (CKM) matrix elements, in terms of the relations between the values of the CKM matrix elements and predictions of the margins of error. The same can be said about the experimental data on the charged lepton decays and massive gauge boson decays. This kind of the structure of the gauge bosons also bring more clarity to the absence of the flavor - changing neutral currents (FCNC). The relation of the fermion masses to the Z boson structure is briefly discussed. The peculiarities of the values of the CKM matrix elements are also emphasized. The interaction Lagrangian built on the basis of the two component spinors type of gauge bosons is scale invariant before the symmetry breaking. The conventional form of the two - point correlation function near the critical point can be obtained by two different methods using this Lagrangian, by applying the CFT approach and the theory of critical exponents approach. It is pointed out that this interaction Lagrange functions near Wilson's renormalization group flow fixed points.